Developing RENATAMA (Reyog Kendang & Etnomathematics) Based on Digital Board Game with Cognitive Psychology Content to Improve Numeracy Literacy - Ajar Dirgantoro; Yepi Sedya Purwananti; Setyo Hartanto; Ajar Dirgantoro; Yepi Sedya Purwananti (Universitas Negeri Malang, 2025)
Mathematical literacy plays an important role in using mathematics to solve real problems. Based on the PISA results, Indonesia's mathematical literacy is currently ranked in the bottom 15, although in general it has increased compared to the previous year. This is in line with the results of the Minimum Competency Assessment in Tulungagung Regency which shows that numeracy literacy skills are still low. This research aims to: (1) to develop an android application as a learning media in the form of digital board game based on PBL with cognitive psychology content to improve Numeracy Literacy, and (2) to know the feasibility level of the android application as a learning media based on digital board game based on PBL with cognitive psychology content to improve Numeracy Literacy. The application is collaborated with the local cultural content of Reyog Kendang and is acronymised RENATAMA. This research uses the Research and Development (R&D) method using the ADDIE development model. The research subjects included 1 media expert, 1 material expert, and seventh grade students at SMPN 1 Sumbergempol and SMPN 3 Tulungagung. The data collected in the form of qualitative data in the form of interview results and quantitative data in the form of a percentage of feasibility test results. The questionnaire used in this study has aspects that are in accordance with the ISO / IEC 9126 model. The results of this study, show: (1) the RENATAMA (Reyog Kendang & Etnomathematics) based on Digital Board Game with Cognitive Psychology content to improve Numeracy Literacy, and (2) the developed application is declared feasible to use. Feasibility is obtained from the results of the feasibility test with details: (1) Media experts with a percentage of 91.5%; (2) Material experts with a percentage of 96%; (3) Small group test of 88.8%; and (4. Large group test with a percentage of 89%. From the results of this study, it can be categorized as ‘Very Feasible’. So, the android application that has been developed is very feasible to use as a learning media. The advantages are through the use of technology compared to conventional ethnomathematics, originality, adoption of assets and integrated content of culture with mathematics, partnership with regular evaluation, involvement of lecturers and students to encourage the achievement of IKU-PT and being able to motivate themselves according to the goal of increasing numeracy literacy. The novelty is in combining cultural exploration of reyog kendang and PBL-based mathematics with a cognitive psychology approach to improve numeracy literacy, as well as pride in local culture through the RENATAMA.